Humanitarian catastrophe for civilians in northwest Syria. (6th February 2020) - Abbara, Aula; Rayes, Diana; Khalil, Munzer; Kewara, Mazen; Tarakji, Ahmad
Abstract : Nearly 2.7 million people urgently need food and water, shelter, sanitation, and healthcare